Household inflation expectations and consumer spending: Evidence from panel data - Mary A. Burke; Ali Ozdagli (Federal Reserve Bank of Boston, 2020)
Recent research offers mixed results concerning the relationship between inflation expectations and consumption, using qualitative measures of readiness to spend. We revisit this question using survey panel data from the United States of actual spending from 2009 through 2012 that also allow us to control for household heterogeneity. We find that durables spending increases with inflation expectations only for certain types of households, while nondurables spending does not respond to inflation expectations. Moreover, spending decreases with an expected increase in unemployment. These results imply a limited stimulating effect of inflation expectations on aggregate consumption, which could be offset in part or in full if expectations for inflation and unemployment move in the same direction.
Keywords: D12; E52; E58; 330; Inflation expectations; survey data; durable and nondurable goods consumption